Pengaruh Imbangan Pupuk Anorganik dan Pupuk Sipramin terhadap Ketersediaan P dan K serta Hasil Tanaman Padi (Oryza sativaL.) pada Vertisols (Musim Tanam II) - Suntoro Suntoro; Hery Widijanto; Arif Puji Hartanto (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2012)
Title : The Effect of Equally Inorganic Fertilizers and Sipramin on Availability  of P and K and the yield of paddy (Oryza sativa L.) at Vertisols (Plant Season II). This field research conducted from march-august 2005, in Tambakkromo Village, Kecamatan Geneng, Kabupaten Ngawi.The aim of this research was to know the effect of sipramin on availability  of  P and K and the yield of paddy at second plant season. This field experiment used Randomized Complete Block Design with  one factor, consist of 20 treatment, that is: P1 (Sipramin Amina 2000 l.ha-1), P2 (Sipramin Amina 4000 l.ha-1), P3 (Sipramin Amina 2000 l.ha-1 and NPK fertilizer), P4 (Sipramin Amina 2000 l.ha-1 and PK fertilizer), P5 (Sipramin Amina 4000 l.ha-1 and PK fertilizer), P6 (Sipramin Bagitani 2000 l.ha-1), P7 (Sipramin Bagitani 4000 l.ha-1), P8 (Sipramin Bagitani 2000 l.ha-1 and NPK fertilizer), P9 (Sipramin Bagitani 2000 l.ha-1 and PK fertilizer), P10 (Sipramin Bagitani 4000 l.ha-1 and PK fertilizer), P11 (Sipramin Orgami 2000   l.ha-1), P12 (Sipramin Orgami 4000 l.ha-1), P13 (Sipramin Orgami 2000 l.ha-1 and NPK fertilizer), P14 (Sipramin Orgami 2000 l.ha-1 and PK fertilizer), P15 (Sipramin Orgami 4000 l.ha-1 and PK fertilizer), P16 (Sipramin Saritana 2000 l.ha-1), P17 (Sipramin Saritana 4000 l.ha-1), P18 (Sipramin Saritana 2000 l.ha-1 and NPK fertilizer), P19 (Sipramin Saritana 2000 l.ha-1 and PK fertilizer), P20 (Sipramin Saritana 4000 l.ha-1 and PK fertilizer). F-test or Kruskal-Wallis test 1% and 5% was used to know the effect of treatment on experimental result. Duncan multiple range test 5% is used for comparing inter-treatment. For finding out the relation between primary dependent variable and secondary dependent one it is used correlation test. The result of this research indicates that sipramin fertilizer within dose 2000-4000 l.ha-1, with or without N, P, and K fertilizer added, increasing the P and K availability on the soil at the same range with inorganic fertilizer’s used (control) and the apllication of sipramin has a significant effect on yield of paddy, that is, the rice weight per plot. The highest available-P on Bagitani apllication, dose 4000 l/ha with P and K fertilizer added (P10), that is, 0,045%; 0,024% higher than control. The highest available-K on Saritana apllication, dose 2000 l/ha with N, P and K fertilizer added (P10), that is, 0,030%; 0,018% higher than control. Sipramin Saritana 2000 l.ha-1  with N, P, and K fertilizer added (P18) give the highest on yield of paddy, that is, the average rice weight per plot is 4,88 kg, of 0,46 kg higher than control. Equals with 511 kg.ha-1.